GAMBARAN TINGKAT PENGETAHUAN DAN SIKAP REMAJA TENTANG PENCEGAHAN HIV/AIDS - Metaria Nengsih; Arneliwati Arneliwati; Nurul Huda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
HIV/AIDS is sexually transmitted disease caused by the HIV virus (Human Immunodeviciency Virus),the disease is common in productive age such as adolescents. Low knowledge of adolescent madebehavior and attitude of adolescent become not good. This study aims to find out the description ofknowledge and attitude of adolescent about HIV/AIDS prevention. This research used quantitativedescriptive design. This research was conducted at SMAN 9 Pekanbaru to 90 samples taken usedsimple random sampling technique by considering inclusion criteria. The measuring tool used in thisresearch is the questionnaire. The analysis used is univariate analysis conducted to analyze thefrequency distribution of each variable. The result of the research shows that the knowledge ofadolescent high on HIV/AIDS prevention is 51 respondents (56,7%) and high adolescent attitudetoward HIV/AIDS prevention is 46 respondent (51,1%). The results of this study can be a referencefor adolescents to improve knowledge about HIV/AIDS and can address prevention of HIV/AIDStransmission in adolescents.Keywords: Adolescen, Attitude, HIV / AIDS, Knowledge.